Concussion disclosure in middle and high school youth: Who gets the message and are they trained to receive it?. (May 2020) - Wicklund, Alissa; Coatsworth, J Douglas
Background: Disclosure of concussion is vital for proper diagnosis and treatment. Youth have many stakeholders to whom they may disclose concussion, including parents, peers, coaches, and school personnel. We examined whom high school and middle school youth report concussion and the level of concussion education of the recipients of the disclosure. Methods: Data were analyzed from 2362 students, 680 parents, and 150 school personnel who completed an online survey about concussion reporting, education, and training. Results: Youth were most likely to disclose concussions to parents, particularly mothers, and their peer group. Middle school youth reported to teachers and school nurses at higher rates than high school youth. High school youth were more likely to disclose concussion to coaches and athletic trainers than middle school youth. While mothers were the most likely recipient of youths' reporting, they were least likely to have received concussion education. Conclusions: Recipients of youth concussion disclosure differs by school level. Parents are the most common recipients of disclosure. The role of school personnel and coaches changes as youth enter high school. Youth primarily report concussions to parents, yet parents receive the least amount of concussion training. These findings highlight the need for targeted concussion training for stakeholder groups as their role in disclosure may differ by school age.